2020
DOI: 10.1186/s12879-020-05392-x
|View full text |Cite
|
Sign up to set email alerts
|

Epidemiological surveillance of common respiratory viruses in patients with suspected COVID-19 in Southwest China

Abstract: Background The outbreak of coronavirus disease 2019 (COVID-19) caused by the severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) is currently the peak season of common respiratory viral infections. However, the clinical symptoms of most SARS-CoV-2 infected patients are not significantly different from those of common respiratory viral infections. Therefore, knowing the epidemiological patterns of common respiratory viruses may be valuable to improve the diagnostic and therapeutic efficacy of patients … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
27
5
6

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(43 citation statements)
references
References 18 publications
5
27
5
6
Order By: Relevance
“…Increasingly, it is being recognised that during the COVID-19 pandemic, the traditional respiratory virus season has been significantly altered with notable decreases in the incidence of other seasonal respiratory viral infections. 3,7,8 The reasons for this observed significant decrease are not yet fully understood and are likely related, at least in part, to the aforementioned COVID-19 mitigation strategies.…”
Section: Introductionmentioning
confidence: 99%
“…Increasingly, it is being recognised that during the COVID-19 pandemic, the traditional respiratory virus season has been significantly altered with notable decreases in the incidence of other seasonal respiratory viral infections. 3,7,8 The reasons for this observed significant decrease are not yet fully understood and are likely related, at least in part, to the aforementioned COVID-19 mitigation strategies.…”
Section: Introductionmentioning
confidence: 99%
“…Their findings showed that 1% were positive for SARS-CoV-2, with an overall detection rate of other respiratory pathogens of 10%, and rhinovirus also being the most common underlying virus (3%). However, the coinfection rate was higher at 12% [ 14 ]. Notably, coinfections in our samples were observed more commonly with bocavirus (four samples that had coinfections with other respiratory viruses).…”
Section: Discussionmentioning
confidence: 99%
“…were detected [ 28 ]. In a series of 2188 patients, respiratory viruses were identified, mostly Bocavirus, followed by Respiratory Syncytial and Parainfluenza viruses [ 29 ]. However, the boundaries between viral/viral co-colonization, superinfection or successive infections must be clarified.…”
Section: Worldwide Covid-19 Epidemiologymentioning
confidence: 99%